Performance evaluation of a trapezoidal solar pond using magnesium sulphate (MgSO₄) - P. Dineshkumar; M. Raja; M. Venkatesan; M. Dineshkumar (International Journal of Applied Power Engineering (IJAPE), 2026)
Emerging global demand for clean and sustainable energy has intensified research into efficient methods of solar energy capture and storage. Among various renewable energy storage technologies, salt gradient solar ponds (SGSPs) have emerged as a reliable and cost-effective solution. This study presents an advanced experimental evaluation of a trapezoidal SGSP using magnesium sulphate (MgSO₄) as the salinity medium to enhance heat storage performance and system stability. A laboratory-scale trapezoidal pond with a depth of 30 cm was constructed using 18 mm thick plywood and an optimized 16% MgSO₄ concentration (SGSP-M16) was employed to maintain thermal stratification. Experiments conducted over a four-month period in Salem, Tamil Nadu, India, involved detailed energy and temperature analysis across upper convective zone (UCZ), non-convective zone (NCZ), and lower convective zone (LCZ). Results revealed maximum temperature difference of 28 °C among UCZ and LCZ, with LCZ achieving peak energy efficiencies of 25.24%, 26.80%, 28%, and 32.09% from January to April, respectively. These findings confirm the effectiveness of the trapezoidal MgSO₄ based SGSP as a sustainable and scalable system for renewable energy storage and efficient thermal management, suitable for applications such as desalination, greenhouse heating, and industrial preheating.